FEMINISME LIBERAL DALAM NOVEL ENTROK KARYA OKKY MADASARI - Defani Amanda Putri; Sri Budi Astuti (Buana Bastra, 2019)
Feminism or the one known as empasipasi comes from Latin which means woman. Feminism is an awareness of deterrence and the fulfillment of the eremgum dálan maspmiat, the place of work and in the family, and the conscious actions of women and men to change the situation in Okky Madasari's Entrok novel. The purpose of this study is to describe more deeply, adequately and comprehensively about liberal feminism in the novel Entrok by Okky Madasari. The theory used in this study is liberal feminism according to Sugihastuti. The method used in this study is descriptive qualitative research method. The data collection technique of this study uses documentation techniques. The data analysis technique of this research uses descriptive qualitative. The results of the research found in liberal feminism by Okky Madasari's Entrok novel are that literary texts do not have a single meaning, literary texts always produce new interpretations that are not previously thought. In the Entrok novel researchers found that equal rights or inequality among women. Men are powerful and think that women are below them.